1987
DOI: 10.1111/j.1745-4557.1987.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Extractant on L‐ascorbic Acid Recovery From Selected Foods and Beverages

Abstract: Recovery of L-ascorbic acid from selected vegetables, beverages and cereal was determined using up to 3 metaphosphoric acid-containing reagents, 3% trichloroacetic acid (TCA), and cold 0.05 Mperchloric acid (HCIO,). Stability of ascorbic acid in these extractants was monitored over a 4 h holding period. All extractants yielded similar results for the beverages, however, TCA extracts of spinach and HCIO, extracts of tomatoes and cereal produced lower results than the other extractants. L-ascorbic acid content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The AA in bee pollen samples were extracted by metaphosphoric acid (MPA) solution under ultrasonication. It has been demonstrated that MPA is beneficial for the inhibition of AA oxidation [25]. This acidic condition could prevent the formation of ascorbate, and provide a better recovery of AA.…”
Section: Resultsmentioning
confidence: 99%
“…The AA in bee pollen samples were extracted by metaphosphoric acid (MPA) solution under ultrasonication. It has been demonstrated that MPA is beneficial for the inhibition of AA oxidation [25]. This acidic condition could prevent the formation of ascorbate, and provide a better recovery of AA.…”
Section: Resultsmentioning
confidence: 99%
“…The Method 2 extracting solution (based on meta ‐phosphoric acid) was miscible with acetonitrile and DTT, and was used in this work as it was an easier and quicker procedure. Meta ‐phosphoric acid as extracting solution for AA analysis has been reported in previous works, with indications that it precipitates proteins and stabilises AA (Kim et al ., ; Eitenmiller et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…L-AA is liable to degradation and the maintenance of L-AA stability during sample preparation and quantitative analysis has been endeavored by the addition of metaphosphoric acid [24,25]. The quantity of L-AA was not significantly different when 5% metaphosphoric acid solution was used for extraction, followed by incubation in a dark place at 237C for 4 h [25].…”
Section: Minimum Detection Limit Of L-aa and D-iaamentioning
confidence: 99%
“…The quantity of L-AA was not significantly different when 5% metaphosphoric acid solution was used for extraction, followed by incubation in a dark place at 237C for 4 h [25]. The low pH value (pH 5 2) of metaphosphoric acid solution is responsible for the denaturation of ascorbic acid oxidase [24,26] as well as for the stabilization of L-AA in acidic pHs [27].…”
Section: Minimum Detection Limit Of L-aa and D-iaamentioning
confidence: 99%